Computational fluid dynamics of crosswind effect on a flare flame - . Wusnah; . Yunardi; Ilham Maulana; . Elwina; Novi Sylvia; Yazid Bindar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
This paper presents the results obtained from the application of computational fluid dynamics (CFD) to modelling the crosswind effect on a turbulent non-premixed flame. A pre-processor software GAMBIT was employed to set up the configuration, discretisation, and boundary conditions of the flame being investigated.  The commercial software Fluent 6.3 was used to perform the calculations of flow and mixing fields as well as combustion. Standard k-ε and eddy dissipation models were selected as solvers for the representation of the turbulence and combustion, respectively.  The results of all calculations are presented in the forms of contour profiles.  During the investigation, the treatment was performed by setting a constant velocity of fuel at 20 m/s with varied cross-wind velocity and by keeping the cross-wind velocity constant at 1.1 m/s with varied fuel velocity.  The results of the investigation showed that the standard k-ε turbulence model in conjunction with Eddy Dissipation Model representing the combustion was capable of producing reliable phenomena of the flow field and reactive scalars field in the turbulent non-premixed flame being investigated. Other results of the investigation showed that increasing the velocity of the crosswind, when the fuel velocity was kept constant, significantly affected the flow field, temperature and species concentrations in the flare flame. On the other hand, when the velocity of the fuel was varied at the constant crosswind velocity, the increasing velocity of the fuel gave positive impact as it enabled to counteract the effect of crosswind on the flare flame